When is temporal lobe epilepsy not temporal lobe epilepsy? - Engel, Jerome (Brain, 2016)
This scientific commentary refers to ‘Temporal plus epilepsy is a major determinant of temporal lobe surgery failures’, by Barba et al.. (doi:10.1093/brain/awv372).